2016
DOI: 10.1007/s10840-016-0099-4
|View full text |Cite
|
Sign up to set email alerts
|

Getting to zero: impact of electroanatomical mapping on fluoroscopy use in pediatric catheter ablation

Abstract: We have shown a significant decrease in multiple measures of radiation after introduction of C3. Continued refinements are needed to further decrease radiation utilization and achieve the goal of zero fluoroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Consistent with the stochastic mechanism of the radiation related injury, previous observational studies reported increased malignancy rates for both patients undergoing electrophysiological procedures and EP lab staff, with a higher biological harm in the pediatric population . For that reason, emerging zero‐fluoroscopy EP procedures (including AVNRT ablation) using 3‐D EAMs have been increasingly introduced in the EP labs . Nonetheless, the accuracy of the geometries generated by 3‐D EAM systems depends on physical and technical parameters, such as the stability of the reference catheter, intracardiac or thoracic impedance, electromagnetic interference in the EP laboratory, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the stochastic mechanism of the radiation related injury, previous observational studies reported increased malignancy rates for both patients undergoing electrophysiological procedures and EP lab staff, with a higher biological harm in the pediatric population . For that reason, emerging zero‐fluoroscopy EP procedures (including AVNRT ablation) using 3‐D EAMs have been increasingly introduced in the EP labs . Nonetheless, the accuracy of the geometries generated by 3‐D EAM systems depends on physical and technical parameters, such as the stability of the reference catheter, intracardiac or thoracic impedance, electromagnetic interference in the EP laboratory, etc.…”
Section: Discussionmentioning
confidence: 99%
“…EAMs are also associated with higher costs and procedure times as compared to fluoroscopy guidance, though some data have been published indicating a financial noninferiority of the utility of 3‐D‐EAM versus conventional fluoroscopy guidance when considering the high treatment costs of malignant complications of the fluoroscopy exposure . Furthermore, some 3‐D EAM systems require dedicated catheters for mapping and generation of endovascular and endocardial shells (other than the cryo‐ablation catheter), which makes the procedure more expensive .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,12 No groups have reported EAM-only ZFTSP access, but Clark et al have demonstrated that EAM-guided TSP access combined with fluoroscopy is feasible. 6 Reddy et al demonstrated that ICE-guided ZFTSP yielded 90% AF-free success rates at 6.1 months; Montgomery et al follow-up results using the same approach are pending at this time. 11,19 …”
Section: Discussionmentioning
confidence: 99%
“…Obvious group of patients who benefit most from low or ideally ZERO fluoroscopy procedures are children . A larger number of centers have reported their experiences and the use of 3D mapping tools seems to allow a reproducible approach that does not increase the risk of complications (eg, for AV nodal conduction block in AVNRT ablation) . Remote magnetic navigation in young patients seems also result in lesser radiation exposure, a result that has been reported already as one the initial observations using the system in SVT ablation …”
Section: Chapter 14 a Zero‐fluoroscopy Approach To Catheter Ablationmentioning
confidence: 99%